Isotope Effects, Dynamic Matching, and Solvent Dynamics in a Wittig Reaction. Betaines as Bypassed Intermediates - Chen, Zhuo (American Chemical Society, 2014)
[Image: see text] The mechanism of the Wittig reaction of anisaldehyde with a stabilized ylide was studied by a combination of (13)C kinetic isotope effects, conventional calculations, and molecular dynamics calculations in a cluster of 53 THF molecules. The isotope effects support a cycloaddition mechanism involving two sequential transition states associated with separate C–C and P–O bond formations. However, the betaine structure in between the two transition states is bypassed as an equilibrated intermediate in most trajectories. The role of the dynamics of solvent equilibration in the nature of mechanistic intermediates is discussed.